Pemberdayaan Ibu Rumah Tangga Melalui Pelatihan Desain Canva Untuk Usaha Mikro Kecil dan Menengah (UMKM) di Desa Totokaton, Kecamatan Punggur, Kabupaten Lampung Tengah. - Chamdini Putri; Khufyah Robe’nur; Aminatus Sholekah; Anggita Vela (Wisanggeni: Jurnal Pengabdian Masyarakat, 2024)
The development of Micro, Small, and Medium-Sized Enterprises (MSMEs), particularly those run by housewives, has enormous potential in Totokon Village, Punggur District, Central Lampung Regency. However, one of the biggest challenges to improving product attractiveness and digital marketing is the lack of expertise in promotional design. Through design instruction via the user-friendly and accessible Canva app, this business seeks to empower housewives. Intensive training, a participative approach with socialization stages, and help with promotional graphics that meet MSMEs' needs are some of the techniques employed. Digital marketing and community empowerment theory serve as the foundation for this program. The findings demonstrated that participants' abilities to produce eye-catching and expert promotional designs, like logos, flyers, and product catalogs, had improved. Additionally, the participants' confidence in their ability to use social media increased.